Methods for Identifying Substrates of Atypical Mitochondrial Kinases - Barber, Grant (My University, 2012)
Mitochondria are chiefly tasked with the production of ATP. Reversible phosphorylation is postulated to be a central regulatory mechanism in mitochondrial biology, and yet the mitochondrial kinases that perform the phosphorylation events are largely uncharacterized[l]. One group of atypical mitochondrial kinases, the ADCKs (aarF-domain containing kinases), has garnered interest because of the role one of its members play in human disease. Here, we designed and validated a radiolabeling based approach to identify substrates of atypical mitochondrial kinases. To detect labeled proteins, we optimized SDS-PAGE; to detect labeled lipids, we optimized thin layer chromatography (TLC). By manipulating kinase reaction conditions, we reduced background phosphorylation of proteins and lipids by endogenous kinases. From there, we established a high-throughput, in vitro kinase assay to validate kinase-substrate pairs. Our next step is to use this approach to identify substrates of the ADCK family to elucidate their roles in human health and disease.
24 p.
Keywords: Biochemistry